EDUCATION IN BUILDING A HAPPY HOUSEHOLD IN THE PERSPECTIVE OF BUDDHISM - Manggala Wiriya Tantra; Dida Wanti (EDUCATIONAL JOURNAL : General and Specific Research, 2024)
A couple's journey into married life begins with marriage. Marriage, unlike celibacy, requires mutual understanding for the rest of one's life. The reality is that not every marriage is successful. There are different elements that can make strife and even lead detachment or separation. Separate from that happens in homegrown life is something that two or three needs to keep away from. From a Buddhist perspective, this article aims to educate readers on how to live a happy home life until death do us part. This qualitative study employs the literature review method. As a result, the advice in this article is very basic and can help any couple have a happy home life. Marriage is a cheerful life decision joined by responsibility and obligation of both a couple. In order to achieve harmony, creating a happy home requires adequate insight and comprehension.